Analysis of the Prosecutor's Authority Regarding the Dissolution of a Limited Liability Company: A Problem Regarding Persona Standi in Judicio - Akhmad Zaini; Arvrin Desylvia Octavrianas; Salsabila Annisa Nursaputri; Nur Afni; Steppanus Meky Cresiawan (Budapest International Research and Critics University, 2022)
In the existing laws and regulations, it is understood that the Prosecutor has the authority to dissolve a Limited Liability Company, but the reasons for the dissolution have not been comprehensively regulated. This will of course have the potential to affect the legal standing of the Prosecutor in submitting the application. Based on this, the formulation of the problem in this article is First, the authority to dissolve a limited liability company by the prosecutor and Second, the judge's legal considerations (ratio decedendi) regarding the authority to dissolve a limited liability company by the prosecutor. This research is a legal research using statutory approach, conceptual approach, and the case approach. Based on the results of the research in this article, it was found that First, the Prosecutor has the authority to dissolve a Limited Liability Company which has been clearly regulated, both in the PT Law, the Prosecutor's Law, and other laws and regulations, but it is related to the reasons for the dissolution of a Limited Liability Company. By the Prosecutor's Office has not been regulated in detail, especially for reasons of public interest. Second, from the 2 (two) existing decisions, namely the Supreme Court Decision Number 3099 K/Pdt/2017 and the Supreme Court Decision Number 2640 K/Pdt/2019 it can be understood that there are things that must be considered regarding the prosecutor's authority in submitting a request for dissolution limited company.